Ethnobotanical Investigation of Ferula tadshikorum Pimenov in Surkhandarya Region, Uzbekistan - Sharipov, Abdunazar; Samatova, Shokhista; Makhkamov, Trobjon; Karamatova, Gullola; Muydinjon, Muminov; Chorshanbiyev, Farhod; Shokirov, Alisher; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2025)
Background: This article presents the results of an ethnobotanical study of Ferula tadshikorum Pimenov, a plant widely used by the inhabitants of the Surkhandarya region as a green vegetable and medicinal herb. It has been established that F. tadshikorum plays a positive role in the socio-economic life of the population in the mountainous and foothill villages of Surkhandarya region, with its aerial parts being widely consumed as both medicine and food. The destruction of the plant due to resin collection and the cutting of aerial organs during the generative period are the main causes of the decline in its natural reserves. Methods: The ethnobotanical study was carried out using the methodology recommended by T.P. Lebedeva. Initially, 20 villages with a population of more than 50,000 people were selected from four districts of the Surkhandarya region (Uzun, Kumkurgan, Baysun, Sherabad). These villages were chosen based on their proximity to natural populations or plantations of F. tadshikorum. From February 2021 to November 2023, 706 randomly selected respondents aged 20 to 83 were surveyed. Before the questionnaire was conducted, a group discussion was held in each village to explain that the survey was for research purposes. To clarify which species was being discussed, respondents were shown herbarium samples and photographs of F. tadshikorum. The collected questionnaires were analyzed, and the Fidelity Level (FL) was calculated as a quantitative ethnobotanical parameter. Results: The ethnobotanical analysis has revealed a wealth of information about the potential medicinal uses of F. tadshikorum. Based on the analysis, the plant has been documented to be used for eight types of pathological conditions: helminthiasis, flu (acute respiratory viral infections), colds, coughs, constipation, intestinal inflammation, toothache, and oncological diseases. These findings are consistent with studies on the medicinal properties of other Ferula species. Limited research conducted so far has shown that F. tadshikorum possesses cytotoxic, antibacterial, antifungal, and anti-osteoporotic properties. Conclusion: Based on these results, the study concludes that there is a need to promote the rational use of the plant among the local population and to conduct phytochemical and pharmacological research on F. tadshikorum. Key words: Ferula tadshikorum Pimenov, Ethnobotanical knowledge, Surkhandarya region, Uzbekistan.